The Problems Of Student’s Interests In Calculation At Grade IV at SDN 15 Lolong - Syaputra, Arryal; Efendi, Nofriza; Yenti, Linda; Safitri, Nadya (The Future of Education Journal, 2022)
This study aims to determine the interest in counting of grade IV students in learning at SDN 15 Lolong. This type of research uses qualitative methods. Data collected by observation, interview, and documentation techniques. Teacher's research subject class IV and 2 students in class IV. The results of the study show that students' lack of interest in learning and the lack of teachers using media in learning and the limitations of the media for teaching materials and the lack of parental concern for children's learning process at home, thus causing the weak integrity of students